2020
DOI: 10.1111/eje.12524
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dental students’ use of feedback

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…These encouraging results lend weight in clinical education to the pairing of both formal and informal learning and development opportunities which support coaching focused feedback practice that enocourage reflection We contend that a focus on coaching in feedback practice, such as that seen here is also increasingly mindful of the learner perspectives and the complex interplay of personality as part of institutional processes and supports dialogues that may encourage feedback uptake (Freeman et al, 2020 ; Winstone et al, 2017a , b ).These coaching dialogues move away from more traditional, educator centric, feedback practices that include vague, descriptive or evaluative feedback that is generally known to have limited usefulness (Bösner et al, 2017 ; Shaughness et al, 2017 ). Often technology-mediated methods of feedback delivery can encourage a one-way, transmission approach where learners focus on grade rather than feedback and understanding (Carless & Boud, 2018 ; Winstone et al, 2020 ).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…These encouraging results lend weight in clinical education to the pairing of both formal and informal learning and development opportunities which support coaching focused feedback practice that enocourage reflection We contend that a focus on coaching in feedback practice, such as that seen here is also increasingly mindful of the learner perspectives and the complex interplay of personality as part of institutional processes and supports dialogues that may encourage feedback uptake (Freeman et al, 2020 ; Winstone et al, 2017a , b ).These coaching dialogues move away from more traditional, educator centric, feedback practices that include vague, descriptive or evaluative feedback that is generally known to have limited usefulness (Bösner et al, 2017 ; Shaughness et al, 2017 ). Often technology-mediated methods of feedback delivery can encourage a one-way, transmission approach where learners focus on grade rather than feedback and understanding (Carless & Boud, 2018 ; Winstone et al, 2020 ).…”
Section: Discussionmentioning
confidence: 72%
“…This study only examined written feedback in one dental school, it is unclear how these findings would apply in other educational settings. From research, we are aware that similar settings, using similar approaches, experience similar challenges (see, for example, Freeman et al, 2020 ). However application may differ across settings, as exemplified by Bussey and Griffiths ( 2017 ) and further research continues to be warranted in this area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it also promotes civility by timely identifying and dealing with disruptive behaviors in OLE. Qualitative research on understanding students’ use of feedback showed that many students valued feedback to improve their performance regardless of grades or the outcome of the assessment 30 . In contrast, the strategic learners in the same study were disinterested in feedback if they had passing grades 30 …”
Section: Discussionmentioning
confidence: 99%